Virtual Reality as a Teaching and Scientific Dissemination Tool - First results - Tizuca, Michelle Mayumi; Sassi, Victor F. P.; Clua, Esteban W. G.; Medeiros, João P. M.; Tavares, Gabriel; Salgado, Luciana C. C.; Trevisan, Daniela; Sigaud, Lucas M.; Nogueira, Erica C. (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2022: Anais Estendidos do XXIV Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2022.227700, 2022)
Virtual reality has been increasingly widely used in teaching applications, various knowledge areas, and scientific dissemination. Based on this, a collaboration emerged between Casa da Descoberta the Federal Fluminense University's science museum, based at the Physics Institute, and MediaLab, a laboratory specializing in Virtual Reality content at the Computer Science Institute. The original objective was to incorporate a Virtual Reality environment into the museum, so that content from different areas of science is made available to any visitors, including scholars, which are the largest share of visitors. The project includes the installation of several Virtual Reality stations in the museum's physical space and the development of games within the scientific approach. Four games have already been developed and are available for first playing tests presented in this paper.